EFEKTIVITAS TOKSIN BOTULINUM TIPE A TERHADAP SKALA SPASME, SKALA DEPRESI DAN KUALITAS HIDUP PASIEN HEMIFASIAL SPASME DI RSUD CIAWI - Cornelia, Celine; Hamdani, Ismi Adhanisa; Gaharu, Maula N.; Agustina, Lydia (PERDOSNI, 2024)
Introduction: Approximately 10/100.000 individuals worldwide experience hemifacial spasm (HFS) with a ratio of women-to-men at 2:1. Around 90% HFS patients face social life challenges, leading to self-isolation and decreased quality of life. Therapy modalities for HFS include oral therapy, botulinum toxin injection and surgery, but the oral therapy response rate is low. Aim: To determine the effectiveness of botulinum toxin type A injection on, spasm scale, depression scale and quality of life of HFS patients Methods: A quasi-experimental study was conducted at Ciawi Regional Hospital in May-December 2023. Data were collected using a total sampling technique, injection of Clostridium botulinum neurotoxin type A and succeeded by a 2-weeks, 1 month and 2 month follow-up. We used modified Jankovic scale, Mini International Neuropsychiatric Interview and HFS-7 criteria for our instruments. Results: 29 patients are included in this research, aged 30-93 years (31% are male and 69% are female). 69% suffered left-sided HFS and 31% right-sided HFS. 44,8% patients had hypertension. After 2 weeks post-injection, 81.8% patients with 2nd degree HFS and 71.4% patients with 1st degree HFS reported significant symptom improvement (p = 0.046 and 0.025). Both patient’s degree reported depression improvement without significant p-value (p = > 0.05) after 2 weeks until 2 month post injection. Increased quality of life (p = 0.001). Discussion: Clostridium botulinum neurotoxin type A injection is an effective treatment modality to improve spasm, depression and quality of life in HFS patients at Ciawi Regional Hospital. Keywords: Botulinum Toxin, Degree of Spasm, Experimental, Hemifacial Spasm, Quality of Life